A Comparative Study of Knowledge, Attitude, and Determinants of Tuberculosis-Associated Stigma in Rural and Urban Communities of Lagos State, Nigeria. (3rd December 2020) - Oladele, David A.; Balogun, Mobolanle R.; Odeyemi, Kofoworola; Salako, Babatunde L.
Abstract : Background . Tuberculosis (TB) is an important public health concern in Nigeria. TB-associated stigma could lead to delayed diagnosis and care, treatment default, and multidrug resistance. Understanding of TB-associated stigma is therefore important for TB control. The study is aimed at determining and comparing the knowledge, attitude, and determinants of TB-associated stigma. Methodology . This was a comparative cross-sectional study among adults in urban and rural areas of Lagos State, Nigeria. Respondents were selected through a multistage sampling technique and interviewed using a semistructured questionnaire, which contained the Explanatory Model Interviewed Catalogue (EMIC) stigma scale. IBM SPSS Statistics Software package version 20 was used for analysis. Results . A total of 790 respondents were interviewed. High proportions of respondents in rural and urban areas were aware of TB (97.5% and 99.2%, respectively). Respondents in the urban areas had overall better knowledge of TB compared to the rural areas (59.4% vs. 23%; p < 0.001 ), while respondents in the rural areas had a better attitude to TB (60.5% vs. 49.9%; p = 0.002 ). The majority of respondents in rural and urban areas had TB-associated stigma (93% and 95.7%, respectively). The mean stigma score was higher in the urban compared to rural areas (17.43 ± 6.012 and 16.54 ± 6.324, respectively, p = 0.046 ). Marital status and ethnicity were the predictors of TB-associated stigma in the rural communities (AOR-0.257; CI-0.086-0.761; p = 0.014 and AOR–3.09; CI-1.087-8.812; p = 0.034, respectively), while average monthly income and age of respondents were the predictors of TB-associated stigma in urban areas (AOR–0.274; CI–0.009-0.807; p = 0.019 and AOR-0.212; CI–0.057-0.788; p = 0.021, respectively). Conclusion . TB-associated stigma is prevalent in both rural and urban areas in this study. There is therefore a need to disseminate health appropriate information through the involvement of the community. Also, innovative stigma reduction activities are urgently needed.